Sorption Behavior of Dowex PSR-2 and Dowex PSR-3 Resins of Different Structures for Metal(II) Removal. Issue 4 (6th June 2016) - Wołowicz, Anna; Hubicki, Zbigniew
ABSTRACT: The sorption behavior of palladium(II) (Pd(II)) onto strongly basic anion exchange Dowex resins was studied depending on the concentration of hydrochloric acid (0.1–6.0 M HCl–100 mg Pd(II)/L), concentration of hydrochloric and nitric(V) acids (0.1–0.9 M HCl–0.9–0.1 M HNO3 –100 mg Pd(II)/L), and the time of contact of the solution with the anion exchange resin in the batch mode. Similar research was carried out also for the base metal ions such as cobalt(II) (Co(II)), copper(II) (Cu(II)), nickel(II) (Ni(II)), and zinc(II) (Zn(II)). The sorption process was also examined depending on the initial Pd(II) concentration, agitation rate, bead size distribution, and temperature. Pd(II) sorption was also checked in the column mode. The equilibrium and kinetic characteristics of the sorption of Pd(II) with the Dowex PSR-2 and Dowex PSR-3 anion exchange resins were determined. The possibilities of Pd(II) elution and reuse using the batch method was exploited. Pd(II) and Zn(II) sorption on the Dowex resins is time and concentration of acids dependent. Evaluating the determination coefficients, the kinetic studies showed that the pseudo-second-order equation and the Langmuir model described the data more appropriately than others. The maximum sorption capacity was 165.15 mg Pd(II)/g for Dowex PSR-2 and 184.39 mg Pd(II)/g for Dowex PSR-3. Dowex resins give quantitative Pd(II) removal from diluted acidic solutions.